Dynamic portfolio optimization with risk control for absolute deviation model - Yu, Mei; Takahashi, Satoru; Inoue, Hiroshi; Wang, Shouyang (European journal of operational research, 2010)
In this paper, we present a new multiperiod portfolio selection with maximum absolute deviation model. The investor is assumed to seek an investment strategy to maximize his/her terminal wealth and minimize the risk. One typical feature is that the absolute deviation is employed as risk measure instead of classical mean variance method. Furthermore, risk control is considered in every period for the new model. An analytical optimal strategy is obtained in a closed form via dynamic programming method. Algorithm with some examples is also presented to illustrate the application of this model.